2020
DOI: 10.22435/jki.v10i1.1697
|View full text |Cite
|
Sign up to set email alerts
|

Kepuasan Pasien Rawat Jalan terhadap Pelayanan Kefarmasian di Rumah Sakit dan Puskesmas di 11 Provinsi di Indonesia

Abstract: Pharmaceutical services is a direct service and responsible to patients relating to pharmaceutical products aimed to improve the quality of life of patients. Quality of pharmaceutical services can be assessed based on outpatient satisfaction. The aim of the study was to compare the satisfaction of outpatients with pharmaceutical services in hospitals and primary health care. This study used a cross-sectional comparative study design and was conducted in February-November 2017 in 11 provinces, each province con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
1
11

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 2 publications
1
4
1
11
Order By: Relevance
“…sig = 0.000 (<0.05); meaning a significant relationship between the last education and service satisfaction at Kendal General Hospital. This research is not in line with the research of Prihartini et al (2020) (19) at the Indonesian Hospital on "Outpatient Satisfaction with Pharmaceutical Services in Hospitals and Health Centers in 11 Provinces in Indonesia," which stated that educated respondents were satisfied with visiting hours at the hospital. Approx obtained the last education with respondent satisfaction.…”
Section: Relationship Between Last Education and Respondent Satisfactioncontrasting
confidence: 92%
“…sig = 0.000 (<0.05); meaning a significant relationship between the last education and service satisfaction at Kendal General Hospital. This research is not in line with the research of Prihartini et al (2020) (19) at the Indonesian Hospital on "Outpatient Satisfaction with Pharmaceutical Services in Hospitals and Health Centers in 11 Provinces in Indonesia," which stated that educated respondents were satisfied with visiting hours at the hospital. Approx obtained the last education with respondent satisfaction.…”
Section: Relationship Between Last Education and Respondent Satisfactioncontrasting
confidence: 92%
“…From this definition, it can be concluded that in order to satisfy customers, it is necessary to identify what the wants, needs and expectations of customers are so that the sacrifices that have been issued by customers are comparable to what they get and even more (24). Customer satisfaction depends on the extent to which the perceived performance of the product meets customer expectations (25). If the product's performance is lower than customer expectations, the buyer is dissatisfied.…”
Section: Resultsmentioning
confidence: 99%
“…The responsiveness component reflects an institution's commitment to deliver quick service to its customers [13]. The term "responsiveness" refers to a patient's appraisal of the Pharmacist at Private Dental Hospital's ability to respond to the demands of visiting patients.…”
Section: Responsiveness Aspectsmentioning
confidence: 99%